Technologies and methods of business processes analysis and optimization (Revista de Investigaciones Universidad del Quindío, 2022)
The process approach to management is based on the automation of various aspects of the company's activities. The formation, optimization, restructuring and improvement of business processes are taking place along with the introduction of applied systems (most often, on 1C: Enterprise platform). Nevertheless, business analysts play a key role in optimizing a company's business processes. The study intends to scrutinize the technologies and methods of business processes analysis and optimization.  To that end, monographic, economic-statistical, and abstract-logical methods are employed. Based on the results, in the context of the optimization methodology, optimization can be considered in the framework of progressive improvement or reengineering of business processes (global, large-scale revision of the system). The study of the optimization methodology for business processes revealed several elements of this process, including the choice of methods of analysis and optimization of business processes, ranking of business processes by their importance to show priority processes to start optimization with, and finally, development of a system of key performance indicators to link the personnel motivation system with the achievement of tactical and strategic goals of the company.
Keywords: Business Processes; Key Performance Indicators; Ranking Of Business Processes; Depreciation